POLA NAMA DESA DI KABUPATEN PONOROGO PADA ERA ADIPATI RADEN BATORO KATONG: SEBUAH TINJAUAN ETNOLINGUISTIK - Alip Sugianto (Universitas Stikubank (UNISBANK) Semarang, 2017)
This research is about the Pattern Name of villages in Ponorogo At Duke Era Raden Katong Batoro which aims to know about the morphological word formation and meaning so that they could know the historical and cultural values of local communities as a historical process in the past in the frame etnolinguistic. Research data were obtained from two books, namely Ponorogo Chronicle Books Warok Purwowijoyo Work Volume 1 (1985) and a book entitled Empire Wengker and Reyog Ponorogo Warok Moelyadi Work (1986). Research shows that the name of the village in Ponorogo categorically, there are four types based on the figure, title, building and important events at the time of Batoro Katong. In addition, the names of the village are morphologically included zero derivation, affixation, composition and abbreviation. The historical significance which can be identified by its culture turns names the village come from the names of People Punggawa Raden Batoro Katong who have rendered and established Ponorogo, other than that the place where the village name is categorized building which can be identifying that a strong presumption formerly the place actually where the name of the building is located while the name of the village is a significant event that occurred at the time immortalized as the name of the village to remember the struggle of Raden Katong Batoro, the founding father of Ponorogo.Keywords: Village Name and Etnolinguistic